2021
DOI: 10.3390/plants10010084
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Pressure and Climate Change on the Habitat Availability and Protection of Cypripedium (Orchidaceae) in Northeast China

Abstract: Human pressure on the environment and climate change are two important factors contributing to species decline and overall loss of biodiversity. Orchids may be particularly vulnerable to human-induced losses of habitat and the pervasive impact of global climate change. In this study, we simulated the extent of the suitable habitat of three species of the terrestrial orchid genus Cypripedium in northeast China and assessed the impact of human pressure and climate change on the future distribution of these speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…According to previous research, human pressure has had an important impact on the distribution of some Cypripedium orchid species [8]. In this study, we also found that the population density (POP)-an index of human pressure or human activity-was a crucial factor in explaining the distribution of Brachypetalum orchid species in southwest China.…”
Section: Relationships Between Environmental Factors and The Distribution Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 55%
See 3 more Smart Citations
“…According to previous research, human pressure has had an important impact on the distribution of some Cypripedium orchid species [8]. In this study, we also found that the population density (POP)-an index of human pressure or human activity-was a crucial factor in explaining the distribution of Brachypetalum orchid species in southwest China.…”
Section: Relationships Between Environmental Factors and The Distribution Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 55%
“…As one of the global biodiversity hotspots [6], southwest China has a high level of orchid diversity [2], but the majority of these species are under threat. Furthermore, many orchids are significant in the horticultural industry for their unique and attractive flowers, such as Paphiopedilum villosum [7] and Cypripedium macranthos [8]. Moreover, several orchid species, such as Dendrobium crepidatum [9] and Bletilla striata [10], also have relatively high medicinal value, particularly in traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…D. L, Fu [13]. Among these models, the Maxent model has shown many advantages over other models when applied to "existence-only" species occurrence data, and is widely used for species distribution prediction and habitat suitability assessment [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%